ナンキョク ショウワ キチ デノ チョウオンパ フウソク オンドケイ ニヨル タイキ ランリュウ カンソク - 真木, 太一; マキ, タイチ; MAKI, Taichi (国立極地研究所, 1974)
P(論文) The atmospheric turbulence in stable stratification was observed at Syowa Station in Antarctica during the period from February to December in 1970. Characteristics of atmospheric turbulence are analyzed in relation to the stability or the wind speed at the height of 20 m in surface air layer. Obtained results are as follows: U_<20> (horizontal mean wind speed at the height of 20m) is proportional to about -0.56 power of Ri (Richardson number). W_<20>/U_<20> (ratio of the vertical mean wind speed to U_<20> at the height of 20m) is independent of Ri. The standard deviation of the longitudinal wind speed (σ_U) is in direct proportion to the standard deviation of the lateral wind speed (σ_v). The relations between σ_U and σ_w (standard deviation of vertical wind speed) and between σ_v and σ_w are expressed with the two different equations, which have each transition point. Gustiness decreases with the increase of U_<20> below 8.5 m/s (U_<20>) and has a constant value above 8.5 m/s. Gust factor for five minutes decreases with the increase of U_<20>. The characteristic frequency distributions of three-dimensional wind components were made clear in comparison with the three typical weather condition. The Monin- Obukhov length and the energy dissipation rate increases in proportion to about -1.4 power of Ri and to about 2.7 power of U_<20> respectively in stable stratification. The characteristic time scales of longitudinal, lateral and vertical wind components increase with the increase of Ri and decrease with the increase of U_<20>, and the ratios of proportional components represent the cubic vortex, i.e., length:breadth:height = 6.3 : 1.9 : 1. The value of m obtained from Eq. (7) increases with the increase of Ri. departmental bulletin paper